Jacques Derrida’s Interpretation of Pharmakon - Urbonienė, Aušra (Problemos, 2009)
The article deals with Derrida’s interpretation of Plato’s notion of pharmakon. Pharmakon is the Greek word which has two opposite meanings – “cure” and “poison”. The concept of pharmakon, according to Derrida, produces a play of binary oppositions crucial to Western logocentric tradition: remedy/poison, speech/writing, good/bad, interior/exterior, etc. In Plato’s Pharmacy Derrida questions the main distinction between speech and writing. He argues that speech was viewed as the “original” form of language by Plato and the Western tradition. Writing is a later development – essentially bad, external to memory, productive not of truth but of appearances. Derrida, in his theory of archi-writing, turns upside down the opposition by showing that speech is a form of writing. Also, when reading Plato, Derrida reveals an interconnection between the words pharmakon (remedy), pharmakeus (sorcerer, magician) and pharmakos (scapegoat) which was never used by Plato but, according to Derrida, plays an important role in the character of Socrates. Socrates as pharmakeus becomes the most famous pharmakos in Athens after he drinks the pharmakon.